B cell antigen receptor signalling in the balance of tolerance and immunity. - Cornall, R; Goodnow, C (1998)
The quantity and quality of signals from the B cell antigen receptor (BCR) drives the positive and negative selection of B lymphocytes and establishes the balance of tolerance and immunity. Experiments using immunoglobulin transgenic mice and mutations in key BCR signalling components have given insight into how the antigen receptor is tuned and how thresholds for qualitatively different outcomes are established and maintained. This research also describes how genetic variants can shift the balance between autoimmunity and tolerance.